Two Designated Pathways of Ovarian Cancer and the Crucial Implications to the Treatment - Henny M.A. Rachmasari Putri (Indonesian Socety of Obstetrics and Gynecology, 2009)
Objective: To review the two designated pathways of ovarian cancer and their implications to the management of ovarian cancer. Method: Literature review Result: A proposed carcinogenesis of ovarian cancer has been developed based on a long history of pathological and molecular genetic findings. It divides ovarian cancer as having designated type I or type II pathway. Type I pathway involves ovarian carcinomas with low-grade serous subtype, mucinous, clear cell and endometrioid subtypes. They grow in a stepwise manner, shows low response toward platinum-based chemotherapy and mostly relate to MAPK pathway mutations. High-grade serous ovarian carcinomas which are often found in rapid-aggressive progression with poorer prognosis are suggested as type II pathway. Their major mutations are mainly in TP53. Optimal surgery and adjuvant chemotherapy are the treatment for both confined and advanced cancers. However, the optimal cytoreduction in type II pathway is becoming more important to increase overall survival or disease-free interval. The strategy of screening type II pathway is proposed to be shifted from detection of stage I tumors to detection of minimal ovarian carcinomas probably by biomarkers since the rapid inception is hardly found. Meanwhile the BRCA1/2 screening and classification should be improved for the hereditary breast/ovarian cancer screening. Mutations of KRAS, BRAF, PTEN and CTNNB1 occur majorly in the type I tumors. Therefore, targeted chemotherapy and inhibitor treatments which are investigated foremost in type II recurrence of ovarian malignancies may also be directed to the low response of type I pathway to platinum-based chemotherapy. Conclusion: A different strategy based on the tumorigenesis of ovarian cancer should be considered in term of screening, primary approach and following chemotherapy since there are some distinctive patterns in both pathways. [Indones J Obstet Gynecol 2009;33-4:239-46] Keywords: ovarian cancer, carcinogenesis, screening, cytoreduction, chemotherapy